2015
DOI: 10.1111/jopr.12341
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Types of Moisturizer and Humidity on the Residual Weight and Viscosity of Liquid and Gel Oral Moisturizers

Abstract: Because viscosity of gel moisturizers increases as weight decreases, selecting gel moisturizers with a minimal change in weight and viscosity would be preferable in the case of a long-time application and severe dry mouth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Okura et al examined the relationship between the viscosity and temperature of oral moisturizers and reported that the viscosity of moisturizers fell as their temperature rose . Thus, in the present study, oral moisturizers were stored in an incubator at 37°C to simulate the oral cavity . The growth‐inhibitory zones of the 8‐hour group were significantly smaller than those of the 0‐hour group (except for gel moisturizers), suggesting that the temperature in the incubator affected the antifungal agents in the liquid moisturizers.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Okura et al examined the relationship between the viscosity and temperature of oral moisturizers and reported that the viscosity of moisturizers fell as their temperature rose . Thus, in the present study, oral moisturizers were stored in an incubator at 37°C to simulate the oral cavity . The growth‐inhibitory zones of the 8‐hour group were significantly smaller than those of the 0‐hour group (except for gel moisturizers), suggesting that the temperature in the incubator affected the antifungal agents in the liquid moisturizers.…”
Section: Discussionmentioning
confidence: 89%
“…For patients with dry mouth resulting from radiotherapy or Sjogren's syndrome, pilocarpine and cevimeline are prescribed to promote saliva secretion . These drugs, however, cause adverse side effects such as hyperhidrosis and dyspepsia, so that oral moisturizers are frequently required . In the present study, we focused on the antifungal effects of oral moisturizers to reduce the risk of C. albicans infection, which is common among dry mouth patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations